Shadow into Light: a Bristol-based arts project for bereavement. Issue 1 (2nd January 2016) - Glover, Eleanor; Rice, Gillian; Phillips, Val; Williamson, Claire
Abstract: Shadow into Light (SIL) is a creative and therapeutic art and writing project offering support to bereaved people over a series of 10 sessions. The sessions are facilitated by a poet and artist, with a counsellor also present. They use word and image to investigate and express feelings and assist development of new coping mechanisms, while developing supportive peer relationships. This article outlines the rationale and aims of the project, and gives detail of what was covered in each session and why. Evaluation of the ﬁrst two courses held found that the project was meeting its aims. It is hoped that further research could show statistically signiﬁcant quantitative measures of the effects of the SIL course on participants' mental wellbeing and grief resolution